Hedonic Deficits in Parkinson’s Disease: Is Consummatory Anhedonia Specific? - Loas, Gwenole; duru, cecile; Godefroy, Olivier; krystkowiak, pierre (Frontiers in Neurology, 2014)
Background- Anhedonia, the lowered ability to experience pleasure, is one of the non-motor symptoms of Parkinson’s disease (PD) that is underdiagnosed and consequently undertreated. Few studies have investigated anhedonia in PD by taking into account the influence of socio-demographic variables and versus a control group composed of patients with a pure motor neurologic disease other than PD. The aim of this study was to investigate hedonic deficits in patients with Parkinson’s disease (PD) compared to a control group of patients with non-Parkinson motor neurologic disease (OND), matched for age, gender, level of education and inpatient/outpatient status. Distinctions between anticipatory and consummatory anhedonia and between endogenomorphic and non-endogenomorphic depression were taken into account. Methods- The study population comprised 49 PD patients and 40 subjects with OND. Anhedonia was rated by using the anticipatory (TEPS-ANT) and consummatory (TEPS-CONS) subscales of the Temporal Experience Pleasure Scale (TEPS) and two subscales extracted from the revised Physical Anhedonia Scale (PAS), measuring physical anticipatory (PAS-ANT) and physical consummatory (PAS-CONS) anhedonias. The Snaith Hamilton Pleasure Scale (SHAPS) and the Beck Depression Inventory (BDI-II) were also used together with a subscale extracted from the BDI-II (ENDO-BDI-II) for the diagnosis of endogenomorphic depression. Statistical analyses were performed on the whole group and on the PD group. Results- As hypothesized, several anhedonia scores varied with age and gender in the whole population or in the PD group. On univariate or multivariate analyses, only PAS-CONS was specific for PD and only SHAPS scores differed between depression subtypes in the whole population or the PD group. Conclusion- This study suggests that physical consummatory anhedonia could be specific to PD subjects.